2019
DOI: 10.3390/microorganisms7120692
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Biomarkers and Oral Microbial Load in Relation to the Dental Status of Adults with Cystic Fibrosis

Abstract: The mutation of cystic fibrosis transmembrane conductance regulator (CFTR) can modify the physical and chemical properties of saliva, which in turn can affect the oral microflora and oral health in patients with cystic fibrosis (CF). The aim of the study was to examine oral health status, salivary properties, and total oral bacteria count in CF adults. Dental status was assessed using the decayed missing filled surfaces (DMF-S) index, and oral clearness using the approximal plaque index (API). The Saliva-Check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…However, it is important to understand and consider the consequences of pre-existing systemic diseases or diseases caused by chronic medications on the oral cavity. In patients with cystic fibrosis, observed impaired transport of ions and water transport in exocrine ducts of the salivary glands, modifying of the physical and chemical properties of saliva, and the qualitative and quantitative composition of microbiota inhabiting the oral cavity and affecting its health condition seems significant [48]. Such measures would help to prevent implant failures, especially in patients with CF who receive or plan to receive an implant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to understand and consider the consequences of pre-existing systemic diseases or diseases caused by chronic medications on the oral cavity. In patients with cystic fibrosis, observed impaired transport of ions and water transport in exocrine ducts of the salivary glands, modifying of the physical and chemical properties of saliva, and the qualitative and quantitative composition of microbiota inhabiting the oral cavity and affecting its health condition seems significant [48]. Such measures would help to prevent implant failures, especially in patients with CF who receive or plan to receive an implant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Three main well-known mechanisms: metastatic infection, metastatic injury, and metastatic inflammation explain how the periodontitis is connected with the systemic diseases [2]. Recently, it has been reported that the treatment of the periodontitis improves the systemic diseases [3] and saliva could be used as a biomarker for one of the systemic disease, cystic fibrosis [4]. As described above, the traveling bacteria could cause the systemic diseases and worsen the systemic diseases especially for the patients with underlying diseases.…”
Section: Introductionmentioning
confidence: 99%
“…M: Male, 2 F: Female,3 NS: not significant,4 PD: probing depth,5 CAL: clinical attachment level,6 GI: gingival index,7 PI: plaque; For the Age, PD, CAL, GI, and PI, the difference between two groups was assessed using the Wilcoxon rank sum test. For the Gender, Pearson's Chi-squared test with Yates' continuity correction was used.At the phylum level, the eight most abundant phyla were Firmicutes, Proteobacteria, Actinobacteria, Bacteroidetes, Fusobacteria, Saccharibacteria (TM7), Spirochaetes, and Synergistetes.…”
mentioning
confidence: 99%
“…Beyond the mouth's microbiota, the physiology of the oral cavity is also a factor in CF. Both salivary pH and the pH of the airways in CF are typically lower than those of non-CF individuals [14,15], due in part to malfunction of the CFTR protein, leading to defective secretion of the buffer molecule bicarbonate [16]. The airway microbiota in CF have also shown a decrease in alpha diversity, a measure of the number of organisms present in a sample, and a value that decreases more with diminishing lung function [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%